Corrections to "An Improved Map-Drift Algorithm for Unmanned Aerial Vehicle SAR Imaging" - Huang, Yan; Liu, Feiyang; Chen, Zhanye; Li, Jie; Hong, Wei (IEEE geoscience and remote sensing letters, 2022)
In the above article [1] , the corresponding authors should be Yan Huang and Jie Li.